Research on the handling stability of four-wheel steering vehicle. Issue 5 (June 2019) - Liu, T; Jia, L N; Yang, N; Li, C S
Abstract: Now days, people have higher and higher requirements on automobile performance. As an important performance of a vehicle, the handling stability not only affects the driver's driving experience, but also relates to the safety of the occupants. In order to improve the handling stability of vehicles, a simulation of the four-wheel-steering system in the linear range based on the time domain was conducted in this paper. Sideslip angle and yaw rate were taken as control targets. Proportional feedback control and PID control were integrated in the control system. The comparison of the front-wheel-steering system and the four-wheel-steering system indicated that the four-wheel-steering system had obvious effect on improving the handling stability of the vehicle.